Digital protection for power systems - Johns, Allan 1942-; Salman, S. K. (Salman K.) (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1995)
Digital protection is based on the use of computers in power line relaying. The text covers the mathematical basis of numerical techniques and relay algorithms, the basic elements of digital protection and the fundamentals underlying the commonest algorithmic forms, particularly as applied to line protection. It deals with the fundamentals of travelling-wave techniques and their application to transmission lines, and with digital differential protection of transformers and lines.